Replication data for: The effect of SMS reminders on health screening uptake: a randomized experiment in Indonesia - Marcus, Maja E.; Reuter, Anna; Rogge, Lisa; Vollmer, Sebastian (GRO.data, 2021)
Replication data for "The effect of SMS reminders on health screening uptake: A randomized experiment in Indonesia"